Evaluation of Effect of Ninjin'yoeito on Regional Brain Glucose Metabolism by 18F-FDG Autoradiography With Insulin Loading in Aged Mice - Zhao, Jingmin; Imai, Ryota; Ukon, Naoyuki; Shimoyama, Saki; Tan, Chengbo; Maejima, Yuko; Omiya, Yuji; Takahashi, Kazuhiro; Nan, Guangxian; Zhao, Songji; Ito, Hiroshi; Shimomura, Kenju (Frontiers in Nutrition, 2021)
Introduction: A recent clinical study revealed that Ninjin'yoeito (NYT) may potentially improve cognitive outcome. However, the mechanism by which NYT exerts its effect on elderly patients remains unclear. The aim of this study is to evaluate the effect of Ninjin'yoeito on regional brain glucose metabolism by 18F-FDG autoradiography with insulin loading in aged wild-type mice. Materials and methods: After 12 weeks of feeding NYT, mice were assigned to the control and insulin-loaded groups and received an intraperitoneal injection of human insulin (2 U/kg body weight) 30 min prior to 18F-FDG injection. Ninety minutes after the injection, brain autoradiography was performed. Results: After insulin loading, the 18F-FDG accumulation showed negative changes in the cortex, striatum, thalamus, and hippocampus in the control group, whereas positive changes were observed in the NYT-treated group. Conclusions: Ninjin'yoeito may potentially reduce insulin resistance in the brain regions in aged mice, thereby preventing age-related brain diseases.